Die historische Entwicklung des Lichtfanges. - Lödl, Martin (Contributions to Entomology = Beiträge zur Entomologie, 1989)
The current paper presents a short survey about the history of light-catching-research. Simple experiments with primitive light-sources (e.g. oil-lamps) quickly lead to the usage of powerful electric light during the 19. century. Moreover simple light-traps of the box-type were developed about 100 years ago. In the beginning, only faunistic research was done with light-cathing-methods, but, however, light-catch soon became a modern instrument of ecological and applied entomology. Today, besides the personal light-catch at a white sheet, complex systems, as light-towers or light-traps were used. Especially ecology runs light-traps in combination with selected trap-types, like suction- and pheromone-traps.